Effect of Salvadora persica (Miswak) leaves and stem aqueous extracts on ovarian folliculogenesis and uterine histology in female albino rats - Ahmed Sabry S. Abdoon; H A Abdel-Rahman; O.M Kandil; OA Al-Sagair; AA Mohamed (International Journal of Phytomedicine, 2014)
This work was conducted to evaluate the antifertility activities of Salvadora persica (miswak) aqueous leaves and stem extracts on female albino Wistar rats. Control animals received 0.5 ml of distilled water (Group 1); experimental animals received 0.5 ml of aqueous solution (1:1 w/v) of miswak leaves (Group2) or stem extract (Group 3) for 14 consecutive days. At the end of experiment, animals were weighed and vaginal smears were obtained from control and treated groups. Control and experimental animals were anesthetized then scarified, ovaries and uterus were dissected out, weighed and the number of corpora lutea and surface ovarian follicles were counted. Ovaries and uterus were fixed then processed for paraffin sections and stained with Hematoxylin-eosin. Histological changes in ovaries and uterus were determined. Results showed that administration of miswak leaves or stem aqueous extract is safe and have no side effects or mortalities, and it did not affect body weight of treated animals compared with control. However, administration of miswak leaves or stem aqueous extract significantly decrease (P<0.05) ovarian weight in treated groups. Uterine weight also significantly decreased (P<0.05) after administration of miswak leaves extract compared to control or stem extract groups. Moreover, number of surface ovarian follicles significantly decreased (P<0.05) after exposure to extract of miswak leaves or stem. Number of corpora lutea did not vary between groups. Histological examination revealed that administration of miswak leaves extract caused a significant decrease in the epithelial cell height, myometrial and stromal thickness of uterus compared to stem extract or control group. The present study illustrated the antiovulatory and anti-uterotrophic effects of the aqueous extract of miswak leaves in female rats. This effect may be mediated through direct effect of the extract on the reproductive organs by disruption of ovarian folliculogenesis and inhibiting further development of the recruited ovarian follicles and/or by disruption of the hormonal balance in the hypothalamo-hypophysial ovarian and uterine axis. Miswak stem extract could affect follicular development but it did not affect the uterine structures.